2018
DOI: 10.1159/000489586
|View full text |Cite
|
Sign up to set email alerts
|

Clinicopathological and Prognostic Significance of Cancer Stem Cell Markers in Ovarian Cancer Patients: Evidence from 52 Studies

Abstract: Background/Aims: Relevant markers of cancer stem cells (CSCs) may serve as commonly used biomarkers of ovarian cancer (OC). However, their actual clinicopathological and prognostic significance remains inconclusive. Thus, we conducted a meta-analysis to quantitatively evaluate the association between the expression of CSC-relevant markers (ALDH1, CD117, CD133, and CD44) and OC. Methods: We used an odds ratio (OR) and a hazard ratio (HR) with a 95% confidence interval (CI) to estimate the effects by analyzing 5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
36
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(43 citation statements)
references
References 65 publications
0
36
0
1
Order By: Relevance
“…These analyses are currently "gold standard" assays to measure key CSC properties such as self-renewal and multipotency (52). In support of these preclinical findings, clinical significance of CSCs was recently confirmed by a number of studies demonstrated the association of CSC markers with clinicopathological parameters and clinical outcomes of OC patients (69).…”
Section: Ovarian Cancer Stem Cellsmentioning
confidence: 88%
See 1 more Smart Citation
“…These analyses are currently "gold standard" assays to measure key CSC properties such as self-renewal and multipotency (52). In support of these preclinical findings, clinical significance of CSCs was recently confirmed by a number of studies demonstrated the association of CSC markers with clinicopathological parameters and clinical outcomes of OC patients (69).…”
Section: Ovarian Cancer Stem Cellsmentioning
confidence: 88%
“…Additionally, radio-and chemotherapy treatments have been shown to enrich CSC subpopulations in residual tumors because of selective pressure on drug-resistant cells (65)(66)(67) and due to tumor cell plasticity (64). Even though the CSC state has high plasticity, it is of high clinical importance as a potential marker for clinical outcome and target for anticancer treatment (68,69).…”
Section: The Plasticity Modelmentioning
confidence: 99%
“…11 CD133 and ALDH1A1 are CSC marker that can be identified in OC and correlate with stage in OC. 12 CD133 promote cell proliferation, tumorigenesis, tumor invasion and metastasis through induction of NF-κB and upregulation of MMP9. 13 CD133 is also involved in the activation of the PI3K / Akt and Wnt / β Catenin pathways which induce self renewal potential, tumorigenesis and metastasis.…”
Section: Desi Puspita Et Al / Association Between Expression Of Cd133mentioning
confidence: 99%
“…Ovarian cancer (OC) is an epithelial malignancy of ovary, the seventh most common cancer and the eighth cause of cancerrelated death among women worldwide. 1,2 GLOBOCAN 2012 showed that incidence of OC were 239,000 cases with 152,000 deaths. 2 Incidence of OC is getting higher by year.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation